Factors Associated With Influenza Vaccination Proportion During Pregnancy [23F]. (May 2016) - Kelly, Elizabeth; Power, Michael; Samelson, Renee; Schulkin, Jay
Abstract : INTRODUCTION: ACOG and CDC recommend all pregnant women receive the influenza vaccination (IV). CDC survey data indicate an overall IV rate of 52.2% with a lower rate (42.7%) among non-Hispanic black women. The aim of this study was to document the proportion of pregnant women that receive IV and examine variables which may influence their choice. METHODS: Health records were checked for 415 patients during the 2013–2014 influenza season; 364 patients and 33 providers filled out questionnaires regarding perceptions of IV during pregnancy. RESULTS: Two-thirds (66.7%) of pregnant patients received IV with an additional 7.5% vaccinated before pregnancy. Among patients returning surveys 71.7% reported receiving IV and an additional 3.9% reporting intention to receive IV, with no difference in rate due to race, age or education. Among patients reporting they never (24.8%) receive annual IV, 36.2% reported receiving IV during the current pregnancy. Patient reasons for declining IV were: personal/religious beliefs, concerns about side effects to self or infant and no specific reason or has never received IV. Provider perception of patient refusal included vaccination safety and vaccine not needed. Provider recommendation, prior receipt of IV and patient attitude regarding the safety and efficacy of the vaccine were identified as predictors of whether a patient received IV. Receipt of educational materials was significant in univariate but not multivariate analyses. CONCLUSION: Acceptance of IV was high in this population. Provider consultation has significant influence on pregnant women's acceptance of IV. Providers should be allowed adequate time and resources to counsel patients.